Hybrid electroconvulsive therapy in an adolescent with major depressive disorder: a case report - Zhang, Jing-ya; Li, Jia; Wang, Nan; Xie, Xin-hui; Zeng, Lun (Frontiers in Psychiatry, 2025)
The incidence of depression is increasing in adolescents, who are at a stage of education and therefore more concerned about their cognitive changes. We tried to preserve the rapid relief of depressive symptoms in electroconvulsive therapy (ECT) while causing less cognitive impairment, thus designing the hybrid-ECT (HECT), a modified ECT therapy. Here, we report a case study of a 14-year-old male student with major depressive disorder (MDD) suffering from severe suicidality and significant impairment in social functioning who achieved effective antidepressant effects with HECT and improved cognitive function. HECT showed safety and effectiveness in adolescent MDD patient.